(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Dysfunctions of the endocrine glands due to progressive iron deposition produces different hormone deficiencies in patients with transfusion-dependent thalassemia. With increasing life expectancy, managing complications including endocrine and metabolic complications is becoming important. In this review, we summarized the published original articles from Bangladesh highlighting the endocrine and metabolic complications of patients with thalassemia. In general, evidence is scarce without any reporting regarding glycemic, adrenal, and pituitary status. Endocrinologists should come forward with a team approach involving Hematologists and Transfusion Medicine Specialists to lead this research field further. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2023; 2 (1): 19-23